Synergistic flame retardant prepolymer, its preparation method and application

CN122978432APending Publication Date: 2026-10-27SHANGHAI PRET COMPOSITES +3
View PDF 3 Cites 0 Cited by

Patent Information

Application Number
CN202611266791.1
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2026-08-20
Publication Date
2026-10-27

AI Technical Summary

Technical Problem

该方式虽能从根本上消除阻燃剂颗粒的散射损耗,赋予材料良好的透明性,但阻燃剂引入到分子主链后,会对分子主链的规整性造成破坏,导致材料的力学性能发生下降

Benefits of technology

[0028](1)本发明中协效阻燃预聚物的主链中同时含有磺酸盐结构单元和含磷反应型阻燃结构单元,具有磺酸盐-磷协同阻燃效果,与单独使用磷系阻燃剂相比,达到同样阻燃等级所需的阻燃剂含量更少,进而减少对激光的吸收损耗,提高复合材料的激光透过率。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN122978432A_ABST
    Figure CN122978432A_ABST
Patent Text Reader

Abstract

The application discloses a synergistic flame-retardant prepolymer and a preparation method and application thereof, and belongs to the technical field of composite materials. The preparation method of the synergistic flame-retardant prepolymer comprises the following steps: mixing caprolactam, monocarboxylic acid, amide salt A, amide salt B and deionized water, and then performing ring-opening reaction to obtain the synergistic flame-retardant prepolymer; the prepolymer is a copolymerized nylon prepolymer containing sulfonate structure units and phosphorus-containing reactive flame-retardant structure units; and the prepolymer is subjected to melt blending extrusion together with a nylon resin, glass fibers and a processing aid, so that a high-laser-transmittance halogen-free flame-retardant nylon composite material can be prepared; the vertical burning grade of the nylon composite material is UL94 V-0 level at 1.6 mm, the laser transmittance is greater than or equal to 50% at 2 mm, the nylon composite material has excellent mechanical properties, and has a wide application prospect.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention belongs to the field of composite material technology, specifically relating to a synergistic flame-retardant prepolymer, its preparation method, and its application. Background Technology

[0002] Nylon (polyamide, PA) is widely used in electronics, automotive parts, and other fields due to its excellent mechanical properties and chemical resistance. In many applications, such as electric vehicle battery components, sensor housings, and connectors, not only are halogen-free flame-retardant properties required, but high laser transmittance is also increasingly demanded to meet the requirements of laser welding processes. However, achieving both halogen-free flame retardancy and high laser transmittance in nylon materials presents a challenge. Conventional halogen-free flame-retardant modification methods mainly involve adding halogen-free flame retardants to the nylon matrix, commonly including phosphorus-based, nitrogen-based, and phosphorus-nitrogen synergistic flame retardants. These flame retardants are usually dispersed in particulate form within the nylon matrix, exhibiting a significant difference in refractive index from the matrix and are prone to agglomeration. When a laser passes through such composite materials, the flame retardant particles cause severe light scattering and absorption, leading to a sharp decrease in laser transmittance, which fails to meet the requirements of laser welding processes.

[0003] To improve the laser transmittance of halogen-free flame-retardant nylon composites, existing technologies mainly employ blending and copolymerization modifications. For blending modification, non-crystalline resins or nucleating agents are typically introduced into the composite system, as seen in patent documents CN117887247A and CN117866430B. The introduction of non-crystalline resins disrupts the regularity of the nylon molecular chains, reducing crystallinity and thus minimizing laser scattering and refraction losses at grain boundaries. Nucleating agents, on the other hand, reduce the grain size of crystalline regions through heterogeneous nucleation, thereby improving laser transmittance. However, such blending modifications only focus on optimizing the crystallization behavior of the matrix resin itself; the scattering of laser light at the interface between the flame retardant and the matrix resin, as well as the absorption by the flame retardant itself, remain unchanged. This results in limited improvement in the laser transmittance of halogen-free flame-retardant nylon composites through traditional blending modifications. Copolymerization modification involves chemically attaching the flame retardant to the nylon molecular backbone, as illustrated in patent document CN122037175A. While this method can fundamentally eliminate the scattering loss of flame retardant particles and impart good transparency to the material, the introduction of flame retardants into the molecular backbone disrupts the regularity of the molecular backbone, leading to a decrease in the material's mechanical properties. Furthermore, the steric hindrance effect of reactive flame retardant monomers places high demands on the process and equipment for copolymerization modification, making it suitable for targeted, customized modifications rather than achieving universal, low-cost, large-scale applications. Summary of the Invention

[0004] Therefore, the main objective of this invention is to provide a synergistic flame-retardant prepolymer that has good compatibility with the nylon resin matrix, reduces the generation of phase interface structures, thereby reducing scattering loss of laser light and improving laser transmittance; it can also serve as a physical crosslinking point to form strong intermolecular forces with the nylon matrix, compensating for the decline in mechanical properties caused by the destruction of molecular chain regularity.

[0005] Another objective of this invention is to provide a method for preparing synergistic flame-retardant prepolymers, which is simple in process and easy to scale up for production.

[0006] Another object of the present invention is to provide an application of a synergistic flame-retardant prepolymer in the preparation of halogen-free flame-retardant nylon composite materials with high laser transmittance.

[0007] To achieve the above objectives, the technical solution adopted by the present invention is as follows:

[0008] In a first aspect, the present invention provides a synergistic flame-retardant prepolymer, comprising or being a copolymer nylon prepolymer containing sulfonate structural units and phosphorus-containing reactive flame-retardant structural units, wherein the copolymer nylon prepolymer has the following structural formula:

[0009]

[0010] In the formula, m is an integer in the interval [20, 41], n is an integer in the interval [2, 4], p is an integer in the interval [5, 10], x is an integer in the interval [8, 16], and y is an integer in the interval [1, 11].

[0011] This invention synthesizes a synergistic flame-retardant prepolymer that can be used to prepare halogen-free flame-retardant nylon composites with high laser transmittance. Because the molecular chain simultaneously contains sulfonate structural units and phosphorus-containing reactive flame-retardant structural units, they can synergistically enhance flame retardancy, improve flame retardancy, reduce the amount of flame retardant used, and thus reduce laser absorption loss. Furthermore, the nylon segments in the prepolymer backbone ensure good compatibility with the nylon resin matrix, and are chemically bonded to the nylon matrix through an amide exchange reaction, further improving compatibility, reducing the formation of interfacial structures, and thus reducing laser scattering loss. Moreover, the sulfonate groups, as strongly polar groups, can form ionic clusters, acting as heterogeneous nucleation sites to promote the reduction of grain size in the crystalline region of the nylon matrix, thereby reducing laser loss and improving laser transmittance; they can also act as physical crosslinking points, forming strong intermolecular forces with the nylon matrix, compensating for the decrease in mechanical properties caused by the disruption of molecular chain regularity.

[0012] Preferably, the relative molecular mass of the synergistic flame retardant prepolymer is 8000-10000 g / mol, and the molecular weight distribution index is 2.0-3.0.

[0013] A second aspect of the present invention also provides a method for preparing a synergistic flame-retardant prepolymer as described in any of the preceding claims, comprising the following steps: mixing caprolactam, a monocarboxylic acid, amide salt A, amide salt B, and deionized water, and then performing a ring-opening reaction to obtain the synergistic flame-retardant prepolymer, wherein:

[0014] Amide salt A is obtained by a salt-forming reaction between sodium isophthalic acid 5-sulfonate and an aliphatic diamine;

[0015] Amide salt B is obtained by salting [(6-oxo-6H-dibenzo[c,e][1,2]oxophosphorylhexane-6-yl)methyl]succinic acid (DDP) and an aliphatic diamine. The purpose of using a monocarboxylic acid is to reduce the end carboxyl group content of the synergistic flame retardant prepolymer, so as to avoid a large number of end carboxyl groups from undergoing depolymerization reaction with the nylon resin matrix during melt extrusion, which would reduce the molecular weight of the resin matrix and affect the mechanical properties.

[0016] Preferably, the monocarboxylic acid is at least one of C2-C12 monocarboxylic acids, and the aliphatic diamine is at least one of C8-C16 diamines.

[0017] Preferably, the molar ratio of caprolactam to monocarboxylic acid is 20-41:1, the mass of amide salt A is 13-20% of the total mass, the mass of amide salt B is 40-50% of the total mass, and the mass of deionized water is 2-3% of the mass of caprolactam.

[0018] Preferably, the ring-opening reaction is carried out at a pressure of 0.01-0.6 MPa, a temperature of 220-260℃, and a time of 4-6 h.

[0019] Preferably, the preparation process of the amide salt A includes: placing sodium isophthalic acid 5-sulfonate, aliphatic diamine, and deionized water in a salt-forming reactor for reaction until the pH value of the system is in the range of 7.2-7.5. The molar ratio of sodium isophthalic acid 5-sulfonate to aliphatic diamine is 1:1.01-1.05, and the amount of deionized water used is 50-80 wt% based on the total mass of sodium isophthalic acid 5-sulfonate, aliphatic diamine, and deionized water; the reaction temperature is 60-95℃, the reaction pressure is 0.1-0.2 MPa, and the reaction is accompanied by stirring at a speed of 100-200 r / min.

[0020] Preferably, the preparation process of the amide salt B includes: placing DDP, aliphatic diamine, and deionized water in a salt-forming reactor for reaction until the pH value of the system is in the range of 7.2-7.5. The molar ratio of DDP to aliphatic diamine is 1:1.01-1.05, and the amount of deionized water used is 50-80 wt% based on the total mass of DDP, aliphatic diamine, and deionized water; the reaction temperature is 60-95℃, the reaction pressure is 0.1-0.2 MPa, and the reaction is accompanied by stirring at a speed of 100-200 r / min.

[0021] A third aspect of the invention also provides the application of the synergistic flame-retardant prepolymer as described in any of the preceding claims for the preparation of a high-laser-transmittance halogen-free flame-retardant nylon composite material. Specifically, nylon resin, the synergistic flame-retardant prepolymer, glass fiber, and additives are melt-blended and extruded to obtain a high-laser-transmittance halogen-free flame-retardant nylon composite material.

[0022] Preferably, the raw materials for the melt blend extrusion include the following components by weight: 53-80 parts of nylon resin, 10-15 parts of synergistic flame retardant prepolymer, 10-30 parts of glass fiber, and 0-2 parts of additives; wherein the nylon resin is nylon 6 and / or nylon 66; the glass fiber is flat glass fiber and / or round glass fiber; and the additives are antioxidants and / or lubricants.

[0023] Preferably, the high laser transmittance halogen-free flame-retardant nylon composite material has a UL94 V-0 vertical flammability rating of 1.6mm and a laser transmittance of ≥50% at 2mm.

[0024] The technical principle of this invention is as follows:

[0025] This invention first designs and synthesizes a synergistic flame-retardant prepolymer containing both sulfonate structural units and phosphorus-containing reactive flame-retardant structural units in its molecular structure. This prepolymer is then melt-blended with nylon resin to obtain a high-laser-transmittance halogen-free flame-retardant nylon composite material. The main chain of the synergistic flame-retardant prepolymer also contains nylon segments, possessing the same or highly similar chemical structure as the nylon resin matrix, ensuring good compatibility between the two. During melt blending, it can undergo an amide exchange reaction with the nylon resin matrix molecular chains. The synergistic flame-retardant prepolymer is chemically bonded to the nylon resin matrix, forming a uniform dispersion at the molecular chain level. This reduces the formation of multiphase interfaces, thereby reducing laser scattering and refraction losses and improving laser transmittance. Since sulfonate groups are strongly polar ionic groups, they can form extremely small ion clusters through electrostatic interactions. Therefore, during the blending and cooling crystallization process, they can act as nucleating agents to induce the crystallization of the nylon resin matrix, forming fine and uniform spherulites, further reducing laser scattering losses. In addition, the ionic clusters formed by sulfonate groups can also serve as physical cross-linking points and form strong interaction forces with the molecular chains of nylon resin matrix, thereby improving the mechanical properties of composite materials and compensating for the decline in mechanical properties caused by the destruction of molecular chain structure.

[0026] In terms of flame retardant performance, it exhibits a synergistic flame retardant effect of sulfonate and phosphorus. At high combustion temperatures, the phosphorus-containing structural units decompose and release active free radicals, which can capture H· and OH· free radicals in the gas-phase combustion chain reaction, interrupting the combustion chain. Simultaneously, it promotes char formation in the condensed phase, enhancing the strength and density of the char layer. Furthermore, the sulfonate structural units generate Lewis acids or strong acidic substances when heated, producing an acid-catalyzed synergistic effect with the phosphorus-containing structural units. This promotes the dehydrogenation and cross-linking of the nylon backbone into char. This synergistic catalysis results in faster and denser char layer formation, further strengthening the flame retardant effect in the condensed phase. Therefore, compared to using phosphorus-based flame retardants alone, a lower flame retardant content is required to achieve the same flame retardant rating, thereby reducing the absorption loss of the flame retardant on the laser and improving the laser transmittance of the composite material.

[0027] Compared with the prior art, the beneficial effects of the present invention are as follows:

[0028] (1) The main chain of the synergistic flame retardant prepolymer in this invention contains both sulfonate structural units and phosphorus-containing reactive flame retardant structural units, which have a synergistic flame retardant effect of sulfonate-phosphorus. Compared with the use of phosphorus-based flame retardants alone, less flame retardant is required to achieve the same flame retardant level, thereby reducing the absorption loss of laser and improving the laser transmittance of the composite material.

[0029] (2) The main chain of the synergistic flame retardant prepolymer in this invention contains nylon segments, which have a similar chemical structure to the nylon resin matrix, ensuring good compatibility between the two. The amide exchange reaction between the prepolymer and the nylon matrix is ​​used to achieve molecular-level chemical bond connection, eliminate multiphase interface, and reduce scattering loss of light absorption.

[0030] (3) In this invention, the ion clusters formed by the sulfonate groups can induce the nylon resin matrix to form fine and uniform spherulites, further reducing the scattering loss of laser light. At the same time, they can also serve as physical crosslinking points to improve intermolecular forces and solve the problem of decreased mechanical properties caused by the destruction of molecular chain structure.

[0031] (4) The method for preparing the synergistic flame retardant prepolymer of the present invention is simple, can be prepared on a large scale in existing equipment, has low cost and high production efficiency, and the prepared composite material has excellent laser transmittance, flame retardant properties and mechanical properties, and has great application prospects. Attached Figure Description

[0032] Figure 1 Melt comparison curves of the high laser transmittance halogen-free flame-retardant nylon composite material prepared in Example 7 and PA6 (M2400, Guangdong Xinhui Meida Nylon Co., Ltd.).

[0033] Figure 2 Crystallization comparison curves of the high laser transmittance halogen-free flame-retardant nylon composite material prepared in Example 7 and PA6 (M2400, Guangdong Xinhui Meida Nylon Co., Ltd.). Detailed Implementation

[0034] The present invention will be further described below with reference to specific embodiments. It should be understood that these embodiments are for illustrative purposes only and are not intended to limit the scope of the invention. Furthermore, it should be understood that after reading the teachings of this invention, those skilled in the art can make various alterations or modifications to the invention, and these equivalent forms also fall within the scope defined by the appended claims.

[0035] The following are the detection methods for relevant performance indicators in each embodiment:

[0036] The relative molecular mass and molecular weight distribution index of the synergistic flame retardant prepolymer were tested by GPC using an Agilent 1260 gel permeation chromatograph with an Agilent HFIP series column. The mobile phase was hexafluoroisopropanol with the addition of sodium trifluoroacetate at a concentration of 0.02 mol / L. The test temperature was 40℃.

[0037] Vertical flammability rating: Tested according to GB / T2408-2021 Determination of flammability of plastics - Horizontal and Vertical methods, with a test strip thickness of 1.6 mm;

[0038] Tensile properties: The test was conducted in accordance with GB / T1040.2-2022 Determination of tensile properties of plastics - Part 2: Test conditions for molded and extruded plastics. The test specimen size was 170mm × 10mm × 4mm.

[0039] Laser transmittance: The laser transmittance performance was tested using an LPKF-TMG3 plastic laser transmittance meter with a laser wavelength of 980nm and a sample thickness of 2.0 mm.

[0040] Example 1

[0041] This embodiment proposes a synergistic flame-retardant prepolymer, and the specific steps are as follows:

[0042] (1) Material preparation:

[0043] DDP, CAS: 63562-33-4;

[0044] Caprolactam;

[0045] Sodium isophthalic acid 5-sulfonate;

[0046] Monocarboxylic acid: hexanoic acid, CAS: 142-62-1;

[0047] Aliphatic diamine: Sebacdiamine, CAS: 646-25-3;

[0048] Deionized water.

[0049] (2) Preparation of amide salts:

[0050] Amide Salt A: Sodium isophthalic acid 5-sulfonate, aliphatic diamine, and deionized water are placed in a salt-forming reactor and reacted until the pH of the system is in the range of 7.2-7.5. The molar ratio of sodium isophthalic acid 5-sulfonate to aliphatic diamine is 1:1.01. Based on the total mass of sodium isophthalic acid 5-sulfonate, aliphatic diamine, and deionized water, the amount of deionized water used is 60 wt%. The reaction temperature is 75℃, the reaction pressure is 0.1 MPa, and the reaction is accompanied by stirring at a speed of 150 r / min.

[0051] Amide Salt B: DDP, aliphatic diamine, and deionized water are placed in a salt-forming reactor and reacted until the pH of the system is in the range of 7.2-7.5. The molar ratio of DDP to aliphatic diamine is 1:1.03. Based on the total mass of DDP, aliphatic diamine, and deionized water, the amount of deionized water used is 60 wt%. The reaction temperature is 80℃, the reaction pressure is 0.1 MPa, and the reaction is accompanied by stirring at a speed of 150 r / min.

[0052] (3) Preparation of synergistic flame-retardant prepolymers:

[0053] A synergistic flame-retardant prepolymer was obtained by mixing caprolactam, monocarboxylic acid, amide salt A, amide salt B and deionized water and carrying out a ring-opening reaction at a pressure of 0.1 MPa and a temperature of 250 °C for 4 h.

[0054] During the reaction, the molar ratio of caprolactam to monocarboxylic acid is 30:1, the mass of amide salt A is 15% of the total mass, the mass of amide salt B is 45% of the total mass, and the mass of deionized water is 2% of the mass of caprolactam.

[0055] The final synergistic flame-retardant prepolymer is composed of a copolymerized nylon prepolymer containing sulfonate structural units and phosphorus-containing reactive flame-retardant structural units. In the structural formula of the prepolymer, m is 30, n is 3, p is 8, x is 10, y is 5, the relative molecular mass is 9000 g / mol, and the molecular weight distribution index is 2.5.

[0056] Comparative Example 1

[0057] This comparative example proposes a synergistic flame-retardant prepolymer, which is basically the same as Example 1, except that in steps (1) and (2), sodium isophthalic acid is used instead of sodium isophthalic acid 5-sulfonate in Example 1.

[0058] The final synergistic flame-retardant prepolymer was composed of a copolymer nylon prepolymer containing phosphorus-containing reactive flame-retardant structural units, with a relative molecular mass of 8200 g / mol and a molecular weight distribution index of 2.5.

[0059] Comparative Example 2

[0060] This comparative example proposes a synergistic flame-retardant prepolymer, which is basically the same as Example 1, except that DDP was not prepared in step (1), amide salt B was not prepared in step (2), and amide salt B was not added in step (3).

[0061] The final synergistic flame-retardant prepolymer was composed of a copolymerized nylon prepolymer containing sulfonate structural units, with a relative molecular mass of 5000 g / mol and a molecular weight distribution index of 3.3.

[0062] Comparative Example 3

[0063] This comparative example proposes a synergistic flame retardant prepolymer, which is basically the same as Example 1, except that in steps (1) and (3), a dicarboxylic acid (adipic acid) is used to replace the monocarboxylic acid (hexanoic acid) in Example 1.

[0064] The final synergistic flame-retardant prepolymer is composed of a copolymer nylon prepolymer containing sulfonate structural units and phosphorus-containing reactive flame-retardant structural units, with a relative molecular mass of 9000 g / mol and a molecular weight distribution index of 2.5.

[0065] Example 2

[0066] This embodiment proposes a synergistic flame-retardant prepolymer, and the specific steps are as follows:

[0067] (1) Material preparation:

[0068] DDP, CAS: 63562-33-4;

[0069] Caprolactam;

[0070] Sodium isophthalic acid 5-sulfonate;

[0071] Monocarboxylic acid: nonanoic acid, CAS: 112-05-0;

[0072] Aliphatic diamine: Dodecanediamine, CAS: 2783-17-7;

[0073] Deionized water.

[0074] (2) Preparation of amide salts:

[0075] Amide Salt A: Sodium isophthalic acid 5-sulfonate, aliphatic diamine, and deionized water are placed in a salt-forming reactor and reacted until the pH of the system is in the range of 7.2-7.5. The molar ratio of sodium isophthalic acid 5-sulfonate to aliphatic diamine is 1:1.03. Based on the total mass of sodium isophthalic acid 5-sulfonate, aliphatic diamine, and deionized water, the amount of deionized water used is 50 wt%. The reaction temperature is 90℃, the reaction pressure is 0.2 MPa, and the reaction is accompanied by stirring at a speed of 100 r / min.

[0076] Amide Salt B: DDP, aliphatic diamine, and deionized water are placed in a salt-forming reactor and reacted until the pH of the system is in the range of 7.2-7.5. The molar ratio of DDP to aliphatic diamine is 1:1.02. Based on the total mass of DDP, aliphatic diamine, and deionized water, the amount of deionized water used is 50 wt%. The reaction temperature is 95℃, the reaction pressure is 0.2 MPa, and stirring is performed during the reaction at a speed of 100 r / min.

[0077] (3) Preparation of synergistic flame-retardant prepolymers:

[0078] A ring-opening reaction was carried out for 4.5 h at a pressure of 0.6 MPa and a temperature of 245 °C after mixing caprolactam, monocarboxylic acid, amide salt A, amide salt B and deionized water to obtain a synergistic flame retardant prepolymer.

[0079] During the reaction, the molar ratio of caprolactam to monocarboxylic acid is 28:1, the mass of amide salt A is 18% of the total mass, the mass of amide salt B is 43% of the total mass, and the mass of deionized water is 3% of the mass of caprolactam.

[0080] The final synergistic flame-retardant prepolymer is composed of a copolymer nylon prepolymer containing sulfonate structural units and phosphorus-containing reactive flame-retardant structural units. In the structural formula of the prepolymer, m is 28, n is 3, p is 7, x is 12, y is 8, the relative molecular mass is 8500 g / mol, and the molecular weight distribution index is 3.

[0081] Example 3

[0082] This embodiment proposes a synergistic flame-retardant prepolymer, and the specific steps are as follows:

[0083] (1) Material preparation:

[0084] DDP, CAS: 63562-33-4;

[0085] Caprolactam;

[0086] Sodium isophthalic acid 5-sulfonate;

[0087] Monocarboxylic acid: Acetic acid, CAS: 64-19-7;

[0088] Aliphatic diamine: Undecanediamine, CAS: 822-08-2;

[0089] Deionized water.

[0090] (2) Preparation of amide salts:

[0091] Amide Salt A: Sodium isophthalic acid 5-sulfonate, aliphatic diamine, and deionized water are placed in a salt-forming reactor and reacted until the pH of the system is in the range of 7.2-7.5. The molar ratio of sodium isophthalic acid 5-sulfonate to aliphatic diamine is 1:1.05. Based on the total mass of sodium isophthalic acid 5-sulfonate, aliphatic diamine, and deionized water, the amount of deionized water used is 80 wt%. The reaction temperature is 65℃, the reaction pressure is 0.15 MPa, and the reaction is accompanied by stirring at a speed of 150 r / min.

[0092] Amide Salt B: DDP, aliphatic diamine, and deionized water are placed in a salt-forming reactor and reacted until the pH of the system is in the range of 7.2-7.5. The molar ratio of DDP to aliphatic diamine is 1:1.05. Based on the total mass of DDP, aliphatic diamine, and deionized water, the amount of deionized water used is 70 wt%. The reaction temperature is 90℃, the reaction pressure is 0.15 MPa, and stirring is performed during the reaction at a speed of 200 r / min.

[0093] (3) Preparation of synergistic flame-retardant prepolymers:

[0094] A synergistic flame-retardant prepolymer was obtained by mixing caprolactam, monocarboxylic acid, amide salt A, amide salt B and deionized water and carrying out a ring-opening reaction at a pressure of 0.01 MPa and a temperature of 220 °C for 6 h.

[0095] During the reaction, the molar ratio of caprolactam to monocarboxylic acid is 41:1, the mass of amide salt A is 13% of the total mass, the mass of amide salt B is 40% of the total mass, and the mass of deionized water is 2% of the mass of caprolactam.

[0096] The final synergistic flame-retardant prepolymer is composed of a copolymer nylon prepolymer containing sulfonate structural units and phosphorus-containing reactive flame-retardant structural units. In the structural formula of the prepolymer, m is 41, n is 3, p is 7, x is 11, y is 1, the relative molecular mass is 10000 g / mol, and the molecular weight distribution index is 2.

[0097] Example 4

[0098] This embodiment proposes a synergistic flame-retardant prepolymer, and the specific steps are as follows:

[0099] (1) Material preparation:

[0100] DDP, CAS: 63562-33-4;

[0101] Caprolactam;

[0102] Sodium isophthalic acid 5-sulfonate;

[0103] Monocarboxylic acid: Undecanoic acid, CAS: 112-37-8;

[0104] Aliphatic diamine: Octyldiamine, CAS: 373-44-4;

[0105] Deionized water.

[0106] (2) Preparation of amide salts:

[0107] Amide Salt A: Sodium isophthalic acid 5-sulfonate, aliphatic diamine, and deionized water are placed in a salt-forming reactor and reacted until the pH of the system is in the range of 7.2-7.5. The molar ratio of sodium isophthalic acid 5-sulfonate to aliphatic diamine is 1:1.03. Based on the total mass of sodium isophthalic acid 5-sulfonate, aliphatic diamine, and deionized water, the amount of deionized water used is 70 wt%. The reaction temperature is 70℃, the reaction pressure is 0.15 MPa, and the reaction is accompanied by stirring at a speed of 200 r / min.

[0108] Amide Salt B: DDP, aliphatic diamine, and deionized water are placed in a salt-forming reactor and reacted until the pH of the system is in the range of 7.2-7.5. The molar ratio of DDP to aliphatic diamine is 1:1.03. Based on the total mass of DDP, aliphatic diamine, and deionized water, the amount of deionized water used is 80 wt%. The reaction temperature is 75℃, the reaction pressure is 0.1 MPa, and stirring is performed during the reaction at a speed of 180 r / min.

[0109] (3) Preparation of synergistic flame-retardant prepolymers:

[0110] A synergistic flame-retardant prepolymer was obtained by mixing caprolactam, monocarboxylic acid, amide salt A, amide salt B and deionized water and carrying out a ring-opening reaction at a pressure of 0.2 MPa and a temperature of 255 °C for 6 h.

[0111] During the reaction, the molar ratio of caprolactam to monocarboxylic acid is 25:1, the mass of amide salt A is 20% of the total mass, the mass of amide salt B is 50% of the total mass, and the mass of deionized water is 2.5% of the mass of caprolactam.

[0112] The final synergistic flame-retardant prepolymer is composed of a copolymer nylon prepolymer containing sulfonate structural units and phosphorus-containing reactive flame-retardant structural units. In the structural formula of the prepolymer, m is 25, n is 4, p is 10, x is 8, y is 6, the relative molecular mass is 10000 g / mol, and the molecular weight distribution index is 2.2.

[0113] Example 5

[0114] This embodiment proposes a synergistic flame-retardant prepolymer, and the specific steps are as follows:

[0115] (1) Material preparation:

[0116] DDP, CAS: 63562-33-4;

[0117] Caprolactam;

[0118] Sodium isophthalic acid 5-sulfonate;

[0119] Monocarboxylic acid: Undecanoic acid, CAS: 112-37-8

[0120] Aliphatic diamine: hexadecanediamine, CAS: 929-94-2

[0121] Deionized water.

[0122] (2) Preparation of amide salts:

[0123] Amide Salt A: Sodium isophthalic acid 5-sulfonate, aliphatic diamine, and deionized water are placed in a salt-forming reactor and reacted until the pH of the system is in the range of 7.2-7.5. The molar ratio of sodium isophthalic acid 5-sulfonate to aliphatic diamine is 1:1.02. Based on the total mass of sodium isophthalic acid 5-sulfonate, aliphatic diamine, and deionized water, the amount of deionized water used is 75wt%. The reaction temperature is 95℃, the reaction pressure is 0.2MPa, and the reaction is accompanied by stirring at a speed of 100r / min.

[0124] Amide Salt B: DDP, aliphatic diamine, and deionized water are placed in a salt-forming reactor and reacted until the pH of the system is in the range of 7.2-7.5. The molar ratio of DDP to aliphatic diamine is 1:1.01. Based on the total mass of DDP, aliphatic diamine, and deionized water, the amount of deionized water used is 65wt%. The reaction temperature is 90℃, the reaction pressure is 0.15MPa, and stirring is performed during the reaction at a speed of 120r / min.

[0125] (3) Preparation of synergistic flame-retardant prepolymers:

[0126] A synergistic flame-retardant prepolymer was obtained by mixing caprolactam, monocarboxylic acid, amide salt A, amide salt B and deionized water and carrying out a ring-opening reaction at a pressure of 0.3 MPa and a temperature of 240 °C for 5 h.

[0127] During the reaction, the molar ratio of caprolactam to monocarboxylic acid is 32:1, the mass of amide salt A is 13% of the total mass, the mass of amide salt B is 40% of the total mass, and the mass of deionized water is 2% of the mass of caprolactam.

[0128] The final synergistic flame-retardant prepolymer is composed of a copolymerized nylon prepolymer containing sulfonate structural units and phosphorus-containing reactive flame-retardant structural units. In the structural formula of the prepolymer, m is 32, n is 2, p is 5, x is 16, y is 10, the relative molecular mass is 8000 g / mol, and the molecular weight distribution index is 2.7.

[0129] Example 6

[0130] This embodiment proposes a synergistic flame-retardant prepolymer, and the specific steps are as follows:

[0131] (1) Material preparation:

[0132] DDP, CAS: 63562-33-4;

[0133] Caprolactam;

[0134] Sodium isophthalic acid 5-sulfonate;

[0135] Monocarboxylic acid: dodecaic acid, CAS: 143-07-7;

[0136] Aliphatic diamine: tetradecanediamine, CAS: 7735-02-6;

[0137] Deionized water.

[0138] (2) Preparation of amide salts:

[0139] Amide Salt A: Sodium isophthalic acid 5-sulfonate, aliphatic diamine, and deionized water are placed in a salt-forming reactor and reacted until the pH of the system is in the range of 7.2-7.5. The molar ratio of sodium isophthalic acid 5-sulfonate to aliphatic diamine is 1:1.03. Based on the total mass of sodium isophthalic acid 5-sulfonate, aliphatic diamine, and deionized water, the amount of deionized water used is 60 wt%. The reaction temperature is 60℃, the reaction pressure is 0.15 MPa, and the reaction is accompanied by stirring at a speed of 120 r / min.

[0140] Amide Salt B: DDP, aliphatic diamine, and deionized water are placed in a salt-forming reactor and reacted until the pH of the system is in the range of 7.2-7.5. The molar ratio of DDP to aliphatic diamine is 1:1.01. Based on the total mass of DDP, aliphatic diamine, and deionized water, the amount of deionized water used is 55 wt%. The reaction temperature is 70℃, the reaction pressure is 0.1 MPa, and the reaction is accompanied by stirring at a speed of 150 r / min.

[0141] (3) Preparation of synergistic flame-retardant prepolymers:

[0142] A synergistic flame-retardant prepolymer was obtained by mixing caprolactam, monocarboxylic acid, amide salt A, amide salt B and deionized water and carrying out a ring-opening reaction at a pressure of 0.4 MPa and a temperature of 260 °C for 5 h.

[0143] During the reaction, the molar ratio of caprolactam to monocarboxylic acid is 20:1, the mass of amide salt A is 20% of the total mass, the mass of amide salt B is 50% of the total mass, and the mass of deionized water is 2% of the mass of caprolactam.

[0144] The final synergistic flame-retardant prepolymer is composed of a copolymer nylon prepolymer containing sulfonate structural units and phosphorus-containing reactive flame-retardant structural units. In the structural formula of the prepolymer, m is 20, n is 3, p is 7, x is 14, y is 11, the relative molecular mass is 8000 g / mol, and the molecular weight distribution index is 2.8.

[0145] Example 7

[0146] This embodiment proposes a method for preparing a halogen-free flame-retardant nylon composite material with high laser transmittance. The specific steps are as follows:

[0147] (1) Raw material preparation:

[0148] Synergistic flame-retardant prepolymer: prepared in Example 1 above;

[0149] Nylon resin: Nylon 6 (M2400, Guangdong Xinhui Meida Nylon Co., Ltd.);

[0150] Glass fiber: flat glass fiber (ECS301HP-3-M4, Chongqing International Composite Materials Co., Ltd.);

[0151] Processing aids: a mixture of antioxidant and lubricant in a 1:1 mass ratio; antioxidant (antioxidant 1098, Tianjin Lianlong New Material Co., Ltd.), lubricant (Licowax OP, Clariant Chemical Co., Ltd.);

[0152] (2) Preparation of high laser transmittance halogen-free flame-retardant nylon composite material

[0153] A high-laser-transmittance halogen-free flame-retardant nylon composite material was obtained by melt blending and extruding nylon resin, synergistic flame-retardant prepolymer, glass fiber, and processing aids.

[0154] The raw materials include the following components by weight: 53 parts nylon resin, 15 parts synergistic flame retardant prepolymer, 30 parts glass fiber, and 2 parts additives.

[0155] The resulting high-laser-transmittance halogen-free flame-retardant nylon composite material achieved a UL94V-0 vertical burning rating at 1.6 mm, a laser transmittance of 55.3% at 2 mm, and a tensile strength of 138.2 MPa. Its melt and crystallization curves compared to nylon 6 are shown below. Figure 1 and Figure 2 As shown.

[0156] Comparative Example 4

[0157] This comparative example presents a method for preparing a halogen-free flame-retardant nylon composite material with high laser transmittance, which is basically the same as Example 7, except that the synergistic flame-retardant prepolymer in this comparative example is the synergistic flame-retardant prepolymer of Comparative Example 1.

[0158] The final high laser transmittance halogen-free flame-retardant nylon composite material achieved a UL94V-2 vertical burning rating at 1.6mm, a laser transmittance of 46.2% at 2mm, and a tensile strength of 112.1MPa.

[0159] Compared to Example 7, the flame retardant properties, laser transmittance, and mechanical properties of the halogen-free flame-retardant nylon composite material prepared in Comparative Example 4 decreased. This is because terephthalic acid was used to replace sodium isophthalate 5-sulfonate in the synergistic flame-retardant prepolymer of Comparative Example 4. This resulted in the lack of sulfonate groups in the synergistic flame-retardant prepolymer, preventing it from forming a synergistic flame-retardant effect with the phosphorus-containing structural units, thus leading to a decrease in flame retardant performance. Furthermore, sulfonate groups can induce grain size refinement in the crystalline region and enhance intermolecular forces. However, the lack of sulfonate groups in Comparative Example 4 resulted in varying degrees of reduction in laser transmittance and tensile strength.

[0160] Comparative Example 5

[0161] This comparative example presents a method for preparing a halogen-free flame-retardant nylon composite material with high laser transmittance, which is basically the same as Example 7, except that the synergistic flame-retardant prepolymer in this comparative example is the synergistic flame-retardant prepolymer of Comparative Example 2.

[0162] The final high laser transmittance halogen-free flame-retardant nylon composite material has no flame-retardant properties, a 2mm laser transmittance of 50.9%, and a tensile strength of 141.3MPa.

[0163] Compared to Example 7, the nylon composite material prepared in Comparative Example 5 exhibited no flame retardant properties, a decrease in laser transmittance, and a certain degree of improvement in tensile strength. This is because the synergistic flame-retardant prepolymer in Comparative Example 5 did not contain DDP for flame retardancy, resulting in a nylon composite material with no flame retardant properties. The addition of DDP disrupts the main chain regularity of the nylon matrix, thus reducing the laser transmittance and increasing the tensile strength of the nylon composite material in Comparative Example 5. However, due to the lack of flame retardant properties, it does not meet the requirements for a high-laser-transmittance halogen-free flame-retardant nylon composite material.

[0164] Comparative Example 6

[0165] This comparative example presents a method for preparing a halogen-free flame-retardant nylon composite material with high laser transmittance, which is basically the same as Example 7, except that the synergistic flame-retardant prepolymer in this comparative example is the synergistic flame-retardant prepolymer of Comparative Example 3.

[0166] The final high laser transmittance halogen-free flame-retardant nylon composite material achieved a UL94V-0 vertical burning rating at 1.6mm, a laser transmittance of 56.7% at 2mm, and a tensile strength of 99.5MPa.

[0167] Compared with Example 7, the tensile strength of the high laser transmittance halogen-free flame-retardant nylon composite material prepared in Comparative Example 6 decreased significantly. This is because the synergistic flame-retardant prepolymer in Comparative Example 6 used a dibasic acid to replace a monobasic acid, which resulted in an excessively high content of terminal carboxyl groups in the synergistic flame-retardant prepolymer. During melt extrusion, the terminal carboxyl groups would undergo a depolymerization reaction with the amide bond, which would reduce the molecular weight of the nylon resin matrix and decrease the intermolecular forces, leading to a significant decrease in the tensile strength of the composite material.

[0168] Comparative Example 7

[0169] This comparative example presents a method for preparing a halogen-free flame-retardant nylon composite material with high laser transmittance, which is basically the same as Example 7, except that: in this comparative example, aluminum diethylphosphinate (Exolit OP1230, Clariant Chemicals Ltd.) is used to replace the synergistic flame-retardant prepolymer in Example 7.

[0170] The final high laser transmittance halogen-free flame-retardant nylon composite material achieved a UL94V-2 vertical burning rating at 1.6mm, a laser transmittance of 31.7% at 2mm, and a tensile strength of 116.3MPa.

[0171] Compared to Example 1, the flame retardant properties, laser transmittance, and tensile strength of the high laser transmittance halogen-free flame-retardant nylon composite material prepared in Comparative Example 7 all decreased. This is because the flame retardant in Example 1 was a synergistic flame retardant with higher flame retardant efficiency, so the content of the added synergistic flame retardant prepolymer was less. However, after replacing it with aluminum diethylphosphonate in Comparative Example 7, the flame retardant efficiency decreased, and the same flame retardant effect could not be achieved with the same content. In addition, aluminum diethylphosphonate dispersed in the nylon resin matrix forms a multiphase structure, and the phase interface generates strong scattering loss to the laser, which seriously weakens the laser transmittance; moreover, aluminum diethylphosphonate dispersed in the nylon resin matrix becomes a stress concentration point, leading to a decrease in tensile strength.

[0172] Example 8

[0173] This embodiment proposes a method for preparing a halogen-free flame-retardant nylon composite material with high laser transmittance. The specific steps are as follows:

[0174] (1) Raw material preparation:

[0175] Synergistic flame-retardant prepolymer: prepared in Example 2 above;

[0176] Nylon resin: a mixture of nylon 66 and nylon 6 in a mass ratio of 1:1; nylon 66 (EPR24, Pingdingshan Shenma Engineering Plastics Co., Ltd.), nylon 6 (M2400, Guangdong Xinhui Meida Nylon Co., Ltd.).

[0177] Glass fiber: flat glass fiber (ECS301HP-3-M4, Chongqing International Composite Materials Co., Ltd.);

[0178] (2) Preparation of high laser transmittance halogen-free flame-retardant nylon composite material

[0179] A high-laser-transmittance halogen-free flame-retardant nylon composite material was obtained by melt blending and extruding nylon resin, synergistic flame-retardant prepolymer, glass fiber, and processing aids.

[0180] The raw materials include the following components by weight: 80 parts nylon resin, 10 parts synergistic flame retardant prepolymer, and 10 parts glass fiber.

[0181] The final high laser transmittance halogen-free flame-retardant nylon composite material achieved a UL94V-0 vertical burning rating at 1.6mm, a laser transmittance of 58.6% at 2mm, and a tensile strength of 93.5MPa.

[0182] Example 9

[0183] This embodiment proposes a method for preparing a halogen-free flame-retardant nylon composite material with high laser transmittance. The specific steps are as follows:

[0184] (1) Raw material preparation:

[0185] Synergistic flame retardant prepolymer: prepared in Example 3 above;

[0186] Nylon resin: Nylon 66 (EPR24, Pingdingshan Shenma Engineering Plastics Co., Ltd.);

[0187] Glass fiber: Round glass fiber (ECS301HP, Chongqing International Composite Materials Co., Ltd.);

[0188] Processing aids: Lubricant (Licowax OP, Clariant Chemicals Ltd.);

[0189] (2) Preparation of high laser transmittance halogen-free flame-retardant nylon composite material

[0190] A high-laser-transmittance halogen-free flame-retardant nylon composite material was obtained by melt blending and extruding nylon resin, synergistic flame-retardant prepolymer, glass fiber, and processing aids.

[0191] The raw materials include the following components by weight: 66 parts nylon resin, 13 parts synergistic flame retardant prepolymer, 20 parts glass fiber, and 1 part additive.

[0192] The final high laser transmittance halogen-free flame-retardant nylon composite material achieved a UL94V-0 vertical burning rating at 1.6mm, a laser transmittance of 51.7% at 2mm, and a tensile strength of 116.8MPa.

[0193] Example 10

[0194] This embodiment proposes a method for preparing a halogen-free flame-retardant nylon composite material with high laser transmittance. The specific steps are as follows:

[0195] (1) Raw material preparation:

[0196] Synergistic flame-retardant prepolymer: prepared in Example 1 above;

[0197] Nylon resin: Nylon 66 (EPR24, Pingdingshan Shenma Engineering Plastics Co., Ltd.);

[0198] Glass fiber: Flat glass fiber (ECS301HP-3-M4, Chongqing International Composite Materials Co., Ltd.)

[0199] Processing aids: Antioxidant (Antioxidant 1098, Tianjin Lianlong New Material Co., Ltd.);

[0200] (2) Preparation of high laser transmittance halogen-free flame-retardant nylon composite material

[0201] A high-laser-transmittance halogen-free flame-retardant nylon composite material was obtained by melt blending and extruding nylon resin, synergistic flame-retardant prepolymer, glass fiber, and processing aids.

[0202] The raw materials include the following components by weight: 62 parts nylon resin, 12 parts synergistic flame retardant prepolymer, 25 parts glass fiber, and 1 part additive.

[0203] The final high laser transmittance halogen-free flame-retardant nylon composite material achieved a UL94V-0 vertical burning rating at 1.6mm, a laser transmittance of 56.6% at 2mm, and a tensile strength of 121.3MPa.

[0204] Example 11

[0205] This embodiment proposes a method for preparing a halogen-free flame-retardant nylon composite material with high laser transmittance. The specific steps are as follows:

[0206] (1) Raw material preparation:

[0207] Synergistic flame-retardant prepolymer: prepared in Example 1 above;

[0208] Nylon resin: Nylon 6 (M2400, Guangdong Xinhui Meida Nylon Co., Ltd.);

[0209] Glass fiber: flat glass fiber (ECS301HP-3-M4, Chongqing International Composite Materials Co., Ltd.);

[0210] Processing aids: a mixture of antioxidant and lubricant in a mass ratio of 8:7; antioxidant (antioxidant 1098, Tianjin Lianlong New Material Co., Ltd.), lubricant (Licowax OP, Clariant Chemical Co., Ltd.);

[0211] (2) Preparation of high laser transmittance halogen-free flame-retardant nylon composite material

[0212] A high-laser-transmittance halogen-free flame-retardant nylon composite material was obtained by melt blending and extruding nylon resin, synergistic flame-retardant prepolymer, glass fiber, and processing aids.

[0213] The raw materials include the following components by weight: 67.5 parts nylon resin, 11 parts synergistic flame retardant prepolymer, 20 parts glass fiber, and 1.5 parts additives.

[0214] The final high laser transmittance halogen-free flame-retardant nylon composite material achieved a UL94V-0 vertical burning rating at 1.6mm, a laser transmittance of 57.1% at 2mm, and a tensile strength of 114.1MPa.

[0215] Example 12

[0216] This embodiment proposes a method for preparing a halogen-free flame-retardant nylon composite material with high laser transmittance. The specific steps are as follows:

[0217] (1) Raw material preparation:

[0218] Synergistic flame-retardant prepolymer: prepared in Example 1 above;

[0219] Nylon resin: Nylon 66 (EPR24, Pingdingshan Shenma Engineering Plastics Co., Ltd.);

[0220] Glass fiber: Round glass fiber (ECS301HP, Chongqing International Composite Materials Co., Ltd.);

[0221] Processing aids: a mixture of antioxidant and lubricant in a 1:1 mass ratio; antioxidant (antioxidant 1098, Tianjin Lianlong New Material Co., Ltd.), lubricant (Licowax OP, Clariant Chemical Co., Ltd.);

[0222] (2) Preparation of high laser transmittance halogen-free flame-retardant nylon composite material

[0223] A high-laser-transmittance halogen-free flame-retardant nylon composite material was obtained by melt blending and extruding nylon resin, synergistic flame-retardant prepolymer, glass fiber, and processing aids.

[0224] The raw materials include the following components by weight: 74 parts nylon resin, 10 parts synergistic flame retardant prepolymer, 15 parts glass fiber, and 2 parts additives.

[0225] The final high laser transmittance halogen-free flame-retardant nylon composite material achieved a UL94V-0 vertical burning rating at 1.6mm, a laser transmittance of 52.3% at 2mm, and a tensile strength of 102.6 MPa.

[0226] The above are merely preferred embodiments of the present invention and are not intended to limit the invention. Various modifications and variations can be made to the present invention by those skilled in the art. Any modifications, equivalent substitutions, or improvements made within the spirit and principles of the present invention should be included within the scope of protection of the present invention.

Claims

1. A synergistic flame-retardant prepolymer, characterized in that, It comprises a copolymer nylon prepolymer containing sulfonate structural units and phosphorus-containing reactive flame-retardant structural units, and the structural formula of the copolymer nylon prepolymer is as follows: In the formula, m is an integer in the interval [20, 41], n is an integer in the interval [2, 4], p is an integer in the interval [5, 10], x is an integer in the interval [8, 16], and y is an integer in the interval [1, 11].

2. The synergistic flame-retardant prepolymer according to claim 1, characterized in that, The relative molecular mass of the copolymerized nylon prepolymer is 8000-10000 g / mol, and the molecular weight distribution index is 2.0-3.

0.

3. The method for preparing the synergistic flame-retardant prepolymer according to claim 1 or 2, characterized in that, include: Caprolactam, monocarboxylic acid, amide salt A, amide salt B and deionized water are mixed and subjected to a ring-opening reaction to obtain a synergistic flame retardant prepolymer. The amide salt A is obtained by a salt-forming reaction of sodium isophthalic acid 5-sulfonate and an aliphatic diamine. The amide salt B is obtained by a salting reaction of [(6-oxo-6H-dibenzo[c,e][1,2]oxophosphorylhexane-6-yl)methyl]succinic acid (DDP) and an aliphatic diamine.

4. The method for preparing the synergistic flame-retardant prepolymer according to claim 3, characterized in that, The monocarboxylic acid is at least one of the C2-C12 monocarboxylic acids, and the aliphatic diamine is at least one of the C8-C16 diamines.

5. The method for preparing the synergistic flame-retardant prepolymer according to claim 3, characterized in that, The molar ratio of caprolactam to monocarboxylic acid is 20-41:1, the mass of amide salt A is 13-20% of the total mass, the mass of amide salt B is 40-50% of the total mass, and the mass of deionized water is 2-3% of the mass of caprolactam.

6. The method for preparing the synergistic flame-retardant prepolymer according to claim 3, characterized in that, The ring-opening reaction is carried out at a pressure of 0.01-0.6 MPa, a temperature of 220-260 ℃, and a time of 4-6 h.

7. The method for preparing the synergistic flame-retardant prepolymer according to claim 3, characterized in that, The preparation process of amide salt A includes: placing sodium isophthalic acid 5-sulfonate, aliphatic diamine, and deionized water in a salt-forming reactor for reaction until the pH value of the system is within 7.2-7.5; wherein, the molar ratio of sodium isophthalic acid 5-sulfonate and aliphatic diamine is 1:1.01-1.05, and the amount of deionized water is 50-80wt% based on the total mass of sodium isophthalic acid 5-sulfonate, aliphatic diamine, and deionized water; the reaction temperature is 60-95℃, the reaction pressure is 0.1-0.2MPa, and the reaction is accompanied by stirring at a stirring speed of 100-200r / min.

8. The method for preparing the synergistic flame-retardant prepolymer according to claim 3, characterized in that, The preparation process of amide salt B includes: placing DDP, aliphatic diamine, and deionized water in a salt-forming reactor for reaction until the pH value of the system is within 7.2-7.5; wherein, the molar ratio of DDP to aliphatic diamine is 1:1.01-1.05, and the amount of deionized water is 50-80wt% based on the total mass of DDP, aliphatic diamine, and deionized water; the reaction temperature is 60-95℃, the reaction pressure is 0.1-0.2MPa, and the reaction is accompanied by stirring at a stirring speed of 100-200r / min.

9. The application of the synergistic flame-retardant prepolymer according to claim 1 or 2, characterized in that, The preparation steps for high laser transmittance halogen-free flame-retardant nylon composite materials include: melt blending and extruding nylon resin, synergistic flame-retardant prepolymer, glass fiber and processing aids to obtain high laser transmittance halogen-free flame-retardant nylon composite materials; wherein the raw materials include the following components by mass parts: 53-80 parts of nylon resin, 10-15 parts of synergistic flame-retardant prepolymer, 10-30 parts of glass fiber, and 0-2 parts of additives. The nylon resin is nylon 6 and / or nylon 66; The glass fiber is a flat glass fiber and / or a round glass fiber; The additives are antioxidants and / or lubricants.

10. The application of the synergistic flame-retardant prepolymer according to claim 9, characterized in that, The high laser transmittance halogen-free flame-retardant nylon composite material has a UL94V-0 vertical flammability rating of 1.6mm and a laser transmittance of ≥50% at 2mm.

Citation Information

Patent Citations

  • A laser-weldable, flame-retardant, yellowing-resistant nylon material and a method for making the same

    CN117866430B

  • Laser-weldable halogen-free flame-retardant polyamide composite material and preparation method thereof

    CN117887247A

  • Halogen-free flame-retardant transparent nylon and preparation method thereof

    CN122037175A